2005
DOI: 10.1016/j.livprodsci.2005.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment tools for the evaluation and improvement of European livestock production systems

Abstract: Different types of assessment tools have been developed in Europe with the purpose of determining the environmental impact of various livestock production systems at farm level. The assessment tools differ in terms of which environmental objectives are included and how indicators are constructed and interpreted. The paper compares typical tools for environmental assessment of livestock production systems, and recommends selected indicators suitable for benchmarking. The assessment tools used very different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 21 publications
2
84
0
2
Order By: Relevance
“…De Vries and De Boer (2010) and Yan et al (2013) warned that some studies consider the emissions or removals due to land use whereas others do not, and some works adopt a "cradle to grave" approach, whereas other studies use a "cradle to gate" approach. Even considering similar objects of analysis, differences in terms of the functional unit definition, allocation methods, and the characterization of the processes were observed (Halberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…De Vries and De Boer (2010) and Yan et al (2013) warned that some studies consider the emissions or removals due to land use whereas others do not, and some works adopt a "cradle to grave" approach, whereas other studies use a "cradle to gate" approach. Even considering similar objects of analysis, differences in terms of the functional unit definition, allocation methods, and the characterization of the processes were observed (Halberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, it was derived from the rule according to which the compliance with the carrying capacity of both local and global ecosystems is a prerequisite to ensure environmental sustainability [7]. This distinction was also proposed by other authors, who called for the use of different environmental performance indicator types (area-based versus product-based) depending on the scale of environmental relevance (local versus global) of the environmental issue considered (e.g., Haas et al [23]; Van der Werf and Petit [24]; De Boer [25]; Halberg et al [26]; Payraudeau and Van der Werf [27]; Blonk et al [28]; Jan et al [19]). …”
Section: Farm Global Vs Local Environmental Performancementioning
confidence: 96%
“…One study (Chen and Corson, 2014), however, was based on data from another included study (Van der Werf et al, 2009), and one study (Halberg et al, 2005) was based on multiple other included studies. These two studies were excluded, resulting in thirteen studies for the comparison.…”
Section: Dairy Cattlementioning
confidence: 99%
“…Two of the four studies tested for statistical differences (Basset-Mens and Van der Werf, 2005;Dourmad et al, 2014). Neither study found a significant difference in GWP between the two systems, whereas energy use was mentioned to be significantly higher (no p-value reported) in Basset-Mens and Van der Werf (2005), but no difference was found in Dourmad et al (2014).…”
Section: Pigsmentioning
confidence: 99%